PENGARUH PENGGUNAAN EVAPORATIVE PAD TERHADAP IKLIM MIKRO PADA RUMAH JAMUR TIRAM (Pleurotus ostreatus) BERDINDING JERAMI DI MUSIM KEMARAU - Dwi Putra, Guyup Mahardhian; Hunaepi, Hunaepi (Bioscientist : Jurnal Ilmiah Biologi, 2014)
In general, oyster mushroom cultivated in the hulls made from black plastic cover. Lack of use of black plastic cover material is its nature that is easily damaged or torn due to the sometimes hot or rainy weather and in the dry season the growth of the fungus is hampered due to low humidity and high air temperature, for it needs a research that aims to anticipate the condition. The purpose of this research is to know the effect of the use of evaporative pad on the home of oyster-walled oyster mushroom in order to maintain its productivity. The methodology used in this study includes the collection of environmental temperature data and room temperature, air humidity, fungus weight, solar radiation. Data analysis used is graphical analysis and statistical analysis. The results show that the evaporative pad produces the best conditions for fungal growth. The method produces an air temperature of 27.33 oC, an air humidity of 92.2%. Results of production in control buildings 814.2 grams and buildings with evaporative pad 1014.5 gr.